2016
DOI: 10.1038/nrc.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

The role of enhancers in cancer

Abstract: Enhancer elements function as the logic gates of the genetic regulatory circuitry. One of their most important functions is the integration of extracellular signals with intracellular cell fate information to generate cell type-specific transcriptional responses. Mutations occurring in cancer often misregulate enhancers that normally control the signal-dependent expression of growth-related genes. This misregulation can result from trans-acting mechanisms, such as activation of the transcription factors or epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
277
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(283 citation statements)
references
References 161 publications
5
277
0
1
Order By: Relevance
“…Tissuespecific enhancers are structurally altered to drive expression of oncogenes (e.g. TMPRSS2-ERG in prostate cancer, IgH -locus alterations in B-cell malignancies, TCR -locus alterations in T-cell malignancies) (Sur and Taipale, 2016). In addition, many oncogenic signaling pathways require cell-specific chromatin contexts (e.g., NOTCH1 activation in T-cell but not B-cell leukemia, and EZH2 activation in B-cell but not T-cell lymphoma).…”
Section: Transcriptional Dysregulation In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Tissuespecific enhancers are structurally altered to drive expression of oncogenes (e.g. TMPRSS2-ERG in prostate cancer, IgH -locus alterations in B-cell malignancies, TCR -locus alterations in T-cell malignancies) (Sur and Taipale, 2016). In addition, many oncogenic signaling pathways require cell-specific chromatin contexts (e.g., NOTCH1 activation in T-cell but not B-cell leukemia, and EZH2 activation in B-cell but not T-cell lymphoma).…”
Section: Transcriptional Dysregulation In Cancermentioning
confidence: 99%
“…Cancer-associated genetic alterations can affect proteins participating in nearly all levels of transcriptional control, including trans -factors (transcription factors, signaling proteins, cofactors, chromatin regulators and chromosome structuring proteins) and cis -elements (enhancers, promoters and insulators) (Figure 3). Many excellent reviews have described an ever-expanding catalogue of these alterations (Bywater et al, 2013; Garraway and Lander, 2013; Kandoth et al, 2013; Lawrence et al, 2014; Stratton et al, 2009; Sur and Taipale, 2016; Vogelstein et al, 2013; Watson et al, 2013). Here we discuss a subset of these alterations, specifically those that lead to the most profound changes in the gene expression program, thereby driving the malignant cell state.…”
Section: Transcriptional Dysregulation In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This maintenance is often disrupted during tumorigenesis, facilitating reversion to less differentiated and more proliferative cell states (Sur and Taipale 2016). We integrated our binding data with gene expression data from The Cancer Genome Atlas Project (TCGA; https://cancergenome.nih.gov) to determine the extent to which these factors regulate genes differentially expressed in cancer.…”
Section: Disruption Of Dap Activity In Hepatocellular Carcinomamentioning
confidence: 99%
“…Turning to the enhancer project, recent large genome-wide association studies (GWAS) have demonstrated that most of the genetic variants which predispose to cancer, reside inside of putative enhancer elements [117,151]. Mutations of binding motifs for the MYB TF are associated with increased enhancer activity and involved in T cell acute lymphoblastic leukaemias [152].…”
Section: Resultsmentioning
confidence: 99%